Decoerência de sistemas quânticos induzida por cadeias de spin - Leonardo da Silva Souza (2015)
In this work we studied the decoherence in a central quantum system S uniformly coupled to a reservoir R, chosen as a quantum Ising chain with transverse field. Initially, we review the usual approach to diagonalize the quantum Ising Hamiltonian. We investigate some properties of the gap (energy gap between the lower energy state of the positive and negative parity subspace). We consider the system S as a two-level system and study the Loschmidt echo (EL) behavior, which for this model configuration may be use to characterize the decoherence. We show that LE decay sharply when the reservoir R is near the critical value of the transverse field. Finally, we assume the system S as a arbitrary spin-s system and study how the choice of s affect quantum-classical transition of the model.